A review on Mahalanobis-Taguchi system and time-driven activity-based costing for production environment - Nor Suhadah, Razali; Mohd Yazid, Abu; S. N. A. M., Zaini; N. H., Aris; N. A. M., Halim; E., Sari (Penerbit UMP, 2024)
Mahalanobis-Taguchi system (MTS) is a decision-making system that identifies patterns. The fundamental idea of MTS is to select a set of variables and then apply Mahalanobis distance to optimize each of the factors that contribute to the issue. Meanwhile, time-driven activity-based costing (TDABC) is an approach that defined as a costing model that provides the cost of activities based on the amount of time consumed per activity. The current study seeks to address several gaps and presents research motivation with a particular focus on the potential benefits that comes from employing these two approaches individually in a variety of disciplines. The content of this paper generally consists of studies of literature from 2013 to 2023 from the fields of agriculture, industrial, communication, education, health care, hospitality, and finance sectors. To begin, 74 and 140 research publications employing MTS and TDABC, respectively, have been discovered. From the findings, the industrial sector has the greatest proportion of using MTS technique with 60.81% for 45 from overall 74 articles. MTS is widely used in production environment, as it is a powerful method of optimization that revealed the criticality of parameters, thus can reduce the rejected product in a process. Whereas the health care industry has the largest percentage of articles using the TDABC approach in cost accounting systems, with 62.14% for 87 from total 140 articles. TDABC is popularly applied in health care primarily to estimate the cost of clinical procedures and visits in order to inform operational improvement.